Kemampuan Penyelesaian Soal Cerita Dikaji dari Self-Confidence Peserta Didik di SMP - Ariyani, Dian Frista; Bistari, Bistari; Munaldus, Munaldus (AS-SABIQUN, 2024)
The aim of the research is to describe the ability to solve story problems which is studied from the self-confidence of students at the junior high school level. The method used was a mixed method with a sequential-explanatory model, and involved 30 class VII students. The instruments used include self-confidence questionnaires, story problem solving ability tests and interview references. From the research results, it was revealed that the achievement of self-confidence indicators was based on the classification results into high, medium and low categories, namely at a high level of 4 indicators, a medium level of 3 indicators and a low level of 2 indicators. The ability to solve story problems shown in the high self-confidence category included 6 students, medium 20 students and low 4 students. Achieving high and moderate self-confidence tends to be capable of solving story problems demonstrated by students. In the low category, the failure to achieve indicators of ability to solve story problems is influenced by a lack of ability to calculate to solve problems and not being used to checking again what has been done.